Identification of fungus-responsive cis-acting element in the promoter of Brassica juncea chitinase gene, BjCHI1 - Gao, Ying (Plant science : an international journal of experimental plant biology, 2014)
Copyright © 2013 Elsevier Ireland Ltd. All rights reserved.